2009
DOI: 10.1007/s12192-008-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Hsp70 phosphorylation and PKC-mediated cardioprotection following exercise

Abstract: Both protein kinase C (PKC) activation and Hsp70 expression have been shown to be key components for exercise-mediated myocardial protection during ischemia-reperfusion injury. Given that Hsp70 has been shown to undergo inducible phosphorylation in striated muscle and liver, we hypothesized that PKC may regulate myocardial Hsp70 function and subsequent exercise-conferred cardioprotection through this phosphorylation. Hence, acute exercise of male Sprague-Dawley rats (30 m/min for 60 min at 2% grade) was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 41 publications
(61 reference statements)
1
46
1
2
Order By: Relevance
“…35 During exercise, CHE suppressed the activation of 3 exercise-induced PKC isoforms (PKCα, PKCδ, and PKCε) and attenuated the exercise-mediated reduction of myocardial injury size during ischemia-reperfusion injury. 18 However, recent studies by the present team have shown CHE to have no effect on the cardioprotective effects of EP, and CHE did not attenuate the expression of PKCδ or p-PKCδ Thr507 proteins during EP. 8 In fact, the influence of CHE on the cardioprotective effect is still a point of controversy.…”
Section: Discussioncontrasting
confidence: 54%
“…35 During exercise, CHE suppressed the activation of 3 exercise-induced PKC isoforms (PKCα, PKCδ, and PKCε) and attenuated the exercise-mediated reduction of myocardial injury size during ischemia-reperfusion injury. 18 However, recent studies by the present team have shown CHE to have no effect on the cardioprotective effects of EP, and CHE did not attenuate the expression of PKCδ or p-PKCδ Thr507 proteins during EP. 8 In fact, the influence of CHE on the cardioprotective effect is still a point of controversy.…”
Section: Discussioncontrasting
confidence: 54%
“…Of the mechanisms linked with exercise-induced cardiac protection, Hsp70 has been the most extensively studied, 22,24,34,35 possibly because genetic mouse models of Hsp70 loss-and gain-of-function clearly demonstrate that Hsp70 protects the heart in settings of stress. 26,36,37 In the present study, Hsp70 protein expression was elevated in hearts from Ntg mice after 4 weeks of swim training, as well as trained and untrained caPI3K mice, but not dnPI3K mice ( Figure 4A).…”
Section: Pi3k(p110α) Regulates the Expression Of Genes And Proteins Pmentioning
confidence: 99%
“…In the absence of SSTK, HSP70 antibody detected two bands in the immunoprecipitates, and in the presence of SSTK, the intensity of the lower band of HSP70 decreased, whereas the upper band increased significantly. HSP70 is known to undergo phosphorylation (29), and the SIP-associated HSP70 doublet bands may represent differentially phosphorylated HSP70. To determine whether SIP can directly bind HSP70, we performed binding assays using purified HSP70.…”
Section: Identification Of Sip As An Interactingmentioning
confidence: 99%